PEMBANGUNAN SISTEM AGRIBISNIS DI INDONESIA DAN PERANAN PUBLIC RELATION - SARAGIH, BUNGARAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 1 Februari 2003)
Mistook of economic development strategy in lastime and economic crisis prolonged with various its excess, to compel Indonesia choice alternative strategy in development of economic, which hoped able to give solution of existing problems, without appear new problems. Among some economic development strategy which fulfill the some conditions is Agribusiness Led Development, namely a strategy of economic development which integrate development of agriculture (include estate crop, animal husbandry, fishery, and forestry) with development of agro-industry and linkage services setors. Development strategy of agribusiness system to be convinced able to lead Indonesia economy has competitiveness and sinergys in the world economy. To develop the agribusiness system competitiveness, people-driven, sustainable and decentralized are resposible all of agribusiness stake-holder, suitable with each role. The entreprise is main actors of development agribusiness, the government have a role as facilitator, regulator and promotor of agribusiness development, the researcher have a role to develop of technology, education have a role to increase skill of human resources. Meanwhile, public relation profession have a role to build public good image, for development of agribusiness as well as for firm and agribusiness products. Special about the role of public relation (PR) in development of agribusiness system in Indonesia untill now still not develop yet. Whereas, PR functions very needed in development of agribusiness system, start from macro level till micro level. At macro level, role of PR hoped able to develop good image about importance to develop agribusiness in national economic development.
Keywords: Agribusiness Led Development, Competitiveness, People-driven, Sustainable and Decentralized, Public Relation (PR), Public Good Image